Navigating belief in qadar (destiny) with the contemporary understanding of risk management - Keskin, Zuleyha; Azhar, Rinto Muhammadsyah (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article explores the concept of qadar (destiny) and how it can interplay with contemporary risk management practices, particularly at the personal level. The belief in qadar has implications for how Muslims perceive and approach risks in their everyday lives as they try and @ind the balance between acting on human free will while surrendering to the will of God. The article examines the perspectives of the Maturidi and Ash’ari schools of thought, which both offer similar but yet nuanced differences on what it means to have free will while believing in qadar. Furthermore, the migration of Prophet Muhammad from Mecca to Medina (hijra) is presented as an example of effective risk management in the Islamic tradition. The article concludes by advocating for a better understanding of qadar and the implementation of risk management practices in order to achieve optimal outcomes while recognising the ultimate authority of God.